Alteration of plant immunity in the interaction of roots with the endophytic fungus Phomopsis liquidambaris in response to external nitrogen conditions. Issue 5 (4th August 2022) - Sun, Kai; Tang, Meng‐Jun; Lu, Fan; Peng, Da‐Hong; Xu, Fang‐Ji; Zhang, Wei; Xie, Xing‐Guang; Dai, Chuan‐Chao
Abstract: The complex environments of plants force them to prioritize their immune responses to stimuli occurring simultaneously, including colonization by microbes or nutrient availability. Little is known about how the interplay between endophytes and nutrient status affects the immune responses of both plants and fungi. We primarily monitored immune responses in rice following inoculation with the endophytic fungus Phomopsis liquidambaris under different nitrogen (N) conditions. Ph. liquidambaris promoted plant growth under low N (LN) conditions, concomitant with higher root colonization. Plant production of oxidative signals, including hydrogen peroxide and nitric oxide, was activated by Ph. liquidambaris colonization under LN conditions, while salicylic acid (SA) was maintained at high levels and was involved in controlling rice‐fungal interactions. High N (HN) conditions enhanced the ability of Ph. liquidambaris in suppressing plant cell death and the ability of roots to degrade Ph. liquidambaris cell walls. Furthermore, under both LN and HN conditions, the activity of plant defence‐associated enzymes and fungal antioxidases was not affected in the interactive association. Our data reveal the alteration of plant immunity, including oxidative signalling and plant cell death, by fungal colonization in response to external N conditions and identify SA signalling as a potential controller for rice‐ Ph. liquidambaris interaction.